2016
DOI: 10.1021/jacs.6b06663
|View full text |Cite
|
Sign up to set email alerts
|

Chlorin-Based Nanoscale Metal–Organic Framework Systemically Rejects Colorectal Cancers via Synergistic Photodynamic Therapy and Checkpoint Blockade Immunotherapy

Abstract: Photodynamic therapy (PDT) can destroy local tumors and minimize normal tissue damage, but is ineffective at eliminating metastases. Checkpoint blockade immunotherapy has enjoyed recent success in the clinic, but only elicits limited rates of systemic antitumor response for most cancers due to insufficient activation of the host immune system. Here we describe a treatment strategy that combines PDT by a new chlorin-based nanoscale metal–organic framework (nMOF), TBC-Hf, and a small-molecule immunotherapy agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
259
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 462 publications
(262 citation statements)
references
References 50 publications
(47 reference statements)
3
259
0
Order By: Relevance
“…Release of such cytokines indicates acute inflammation, an important mechanism in inducing antitumor immunity by PDT. 13c,25 High levels of TNF-α, IL-6, and IFN-γ were observed on day 2 post light irradiation in mice treated by ZnP@pyro PDT, indicating that PDT can successfully cause inflammation (Figure 4E). However, 2 days after PDT treatment, all three proinflammatory cytokine levels rapidly dropped to baseline levels, suggesting that inflammation caused by ZnP@pyro PDT was only an acute response.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Release of such cytokines indicates acute inflammation, an important mechanism in inducing antitumor immunity by PDT. 13c,25 High levels of TNF-α, IL-6, and IFN-γ were observed on day 2 post light irradiation in mice treated by ZnP@pyro PDT, indicating that PDT can successfully cause inflammation (Figure 4E). However, 2 days after PDT treatment, all three proinflammatory cytokine levels rapidly dropped to baseline levels, suggesting that inflammation caused by ZnP@pyro PDT was only an acute response.…”
Section: Resultsmentioning
confidence: 97%
“…13 In PDT, a photosensitizer (PS) accumulated in tumors is activated with a specific wavelength of light in the presence of oxygen to generate reactive oxygen species (ROS), predominantly the singlet oxygen ( 1 O 2 ), which kills tumor cells directly by inducing necrosis and/or apoptosis and indirectly by disrupting tumor vasculature and producing tumor-specific immunity. 14 The precise mechanisms involved in PDT-mediated induction of antitumor immunity are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These MOFs uniquely couple with immunogenic phototherapy toward providing synergistic immune responses when loaded with immunomodulatory agents. In 2016, Lin and co‐workers pioneered the first study of nanoscale MOFs for PDT of cancer, which contained heavy metals that facilitated the internetwork crossing of photosensitizers to promote ROS production upon UV exposure as well as incorporation of IDO inhibitors to restore T cell function . The authors showed T cell infiltration in colorectal tumors with effective local and distal tumor rejection, indicating that MOFs can lead to immunogenic cell death by PDT and further potentiate immune checkpoint blockades.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…[263] Platforms designed for combinations of cancer immunotherapy and nonsurgical treatment were reviewed in detail by Nam and colleagues. [271][272][273][274][275][276][277][278] A recent study reported that the combination of PDT and autophagy inhibitor after resection of orthotopic xenograft osteosarcoma observed an enhanced antitumor effect by suppressing PD-L1 expression, which indicated the potential surgical application of photodynamic-immunotherapy to improve outcomes and longterm survivals. [264][265][266][267][268][269][270] The cascaded synergistic effects of photodynamic-immunotherapy can provide a promising strategy to inhibit both primary lesions and distant metastases, which can be hardly achieved by conventional PDT with limited immunologic effects.…”
Section: Postoperative Immunotherapy For Long-term Antitumor Effectsmentioning
confidence: 99%